The timing of growth faltering has important implications for observational analyses of the underlying determinants of nutrition outcomes - Alderman, Harold; Headey, Derek D. (Public Library of Science, 2018)
This studies objectives were to test the prediction that associations between child anthropometric outcomes and various socioeconomic conditions are systematically different for older and younger children. The conclusion is that previous observational analyses appear to substantially underestimate the protective impacts of a wide range of underlying determinants on stunting. Conversely, wasting rates are typically low for children 24–59 months, implying that associations between underlying conditions and wasting may be stronger for children 0–23 months of age. Such analyses should pay closer attention to age disaggregation; researchers should be aware of the age effect reported in the current study and present analysis stratified by age.